Perceived Greenwashing and Consumer Responses in Hospitality: A Cross-National Study of Taiwan and Indonesia - Tz-Li Wang; Risky Pramuja; Aditya Ramadhan Pitlam (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2025)
This study examines the impact of perceived greenwashing on consumer trust, authenticity, satisfaction, and booking intentions in the hospitality industry, with a cross-national comparison between Taiwan and Indonesia. While hotels increasingly adopt sustainability-oriented marketing, the credibility of these claims is often questioned. A structured survey of 428 hotel guests in Taiwan and 462 in Indonesia was conducted to measure perceptions of greenwashing and related consumer responses. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with multi-group analysis. The results demonstrate that perceived greenwashing significantly reduces consumer trust and authenticity, which subsequently diminish satisfaction and booking intentions. Mediation analysis confirmed that both trust and authenticity serve as critical psychological mechanisms transmitting the negative effects of greenwashing to satisfaction outcomes. Multi-group analysis revealed that Taiwanese consumers are more skeptical toward vague sustainability claims, whereas Indonesian consumers exhibit stronger declines in loyalty once trust is compromised. These findings advance greenwashing research by integrating signaling and skepticism theories with authenticity perspectives, while also highlighting the role of cultural and institutional contexts in shaping consumer responses. Practically, the study emphasizes the importance of transparent, verifiable, and authentic sustainability communication for hotels seeking to maintain credibility and secure long-term customer loyalty across diverse markets.